What is Public Engagement and How Does it Help to Address Climate Change? A Review of Climate Communication Research. Issue 3 (3rd April 2022) - Kumpu, Ville
ABSTRACT: This article examines the conceptualization of public engagement in research on climate communication. The review focuses on how public engagement is defined and how its relation to societal change and communication is thematized. In the majority of the reviewed work the term public engagement is used without being explicitly defined. Public engagement, communication, and societal change are approached predominantly from a psychological perspective that emphasizes personal engagement with climate change. The processes that connect what people personally think, feel, and do about climate change to the societal change required adequately to address the issue are rarely elaborated. Communication is predominantly approached as a pragmatic tool that can be used to address climate change rather than an object of theorization. The review concludes with a discussion of sociologically oriented research on climate communication.